Direct ink writing of macroporous lead‐free piezoelectric Ba0.85Ca0.15Zr0.1Ti0.9O3. Issue 6 (3rd December 2018) - Nan, Bo; Olhero, Susana; Pinho, Rui; Vilarinho, Paula M.; Button, Tim W.; Ferreira, José M. F.
Abstract: Direct ink writing (DIW) has become a widespread additive manufacturing technique for material engineering, but its application in lead‐free Ba0.85 Ca0.15 Zr0.1 Ti0.9 O3 piezoelectric ceramics from aqueous systems has not been reported so far to our knowledge. The main obstacle is the high extent of hydrolysis reactions undergone by the starting powders when dispersed in water, hindering the attainment of stable water‐based colloidal suspensions. This paper reports on the preparation of stable aqueous inks from a deagglomerated and surface‐treated powder synthesized by solid‐state reaction and on DIW of macroporous lead‐free piezoelectrics. Based on zeta potential and rheological measurements, the optimal amounts of processing additives (dispersant, binder, and coagulating agent) were selected to transform the initial fluid suspension to a viscoelastic paste with sufficient stiffness and stability for the printing process. Dielectric and piezoelectric properties of samples sintered under different temperatures were also investigated. Abstract : Preparation procedure of lead‐free ink for direct ink writing